Evaluation of 6-year application of the enzymatic colorimetric phenylalanine assay in the setting of neonatal screening for phenylketonuria. In memoriam Horst Bickel. - Schulze, Andreas; Mayatepek, Ertan; Hoffmann, Georg F. (Clinica chimica acta, 2002)
Background: Most reports on phenylketonuria (PKU) screening focused solely on the result of the initial investigation of the neonatal screening sample. The aim of this study was to evaluate an enzymatic phenylalanine (Phe) determination in the whole context spanning from the initial investigation over the recall period, up to the confirmation or exclusion of the disease. Methods: Phe of dried blood spot specimens was analysed colorimetrically in a microtitre-plate assay based on the l-phenylalanine dehydrogenase reaction coupled with an intermediate electron acceptor system. This assay was evaluated for analytical variables and for neonatal PKU screening in a total number of 423,773 neonates during a 6-year period. Results: Method validation with respect to linearity, precision (within-run CVs 3.4-4.2%, between-run CVs 6.2-10.4%), and accuracy fulfilled all requirements for a screening method. Mean Phe (±SD) of 130,000 healthy neonates was 84 (±22) μmol/l with a cut-off point (mean+3 SD) of 150 μmol/l. From 423,773 neonates, hyperphenylalaninemia was confirmed in 155 cases and further differentiated into PKU (41 cases, 27%), BH4 deficiency (3, 2%), non-PKU HPA (67, 43%), transient neonatal HPA (28, 18%), and secondary HPA (16, 10%). The number of false-positives (recall-rate) was 0.23%, and no false-negatives were noted. Conclusions: Detailed studies over a period of 6 years including more than 400,000 neonates clearly show that the enzymatic assay is a reliable and sensitive method for neonatal screening of PKU. The proven prevalence of non-PKU HPA in the German population disclosed by the assay was twice as high as compared to the “Guthrie test” used previously. The growing use and application of tandem mass spectrometry in neonatal screening will not derogate the usefulness of the enzymatic assay in PKU screening in the foreseeable future. Careful analysis of our screening results and monitoring of all pathological samples resulted in an evidence-based flow chart for a rational PKU screening.
Available online 18 October 2001
Gesehen am 30.03.2022